Penyuluhan Warehouse Management pada UMKM melalui Perbaikan secara Berkelanjutan - Monanda Wandita Rini; Nessa Ananda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The business development that is getting faster needs continuous improvements. Implementation of continuous improvement is carried out in large companies and needs to be carried out by MSMEs (Medium Small Micro Enterprises). One activity that needs to be appropriately managed by MSMEs is warehousing. Optimal warehouse management can improve MSME business performance. However, MSMEs do not own knowledge and awareness of continuous improvement optimally. This resulted in warehouse management has not performed optimally by MSMEs. This community service activity aims to provide knowledge to MSMEs about how to identify Muda, Mura, Muri and how to make continuous improvements in warehouse management. Implementing activities is carried out by direct observation and counseling to MSMEs. This community service activity was carried out for two days. The counseling activity was carried out on April 27, attended by owners and employees of Puppet MSMEs in Bogor. The counseling was carried out by providing material on the concept of continuous improvement and identification of Muda, Mura, Muri and continued with a discussion session.